Rancang Bangun Antarmuka berbasis Website Design Method (WDM) untuk Toko Baju Online - Rahmatul Zakia; Tifanny Nabarian; Betty Amalia (Jurnal Informatika Terpadu, 2023)
In Indonesia, the growth of e-commerce is speedy; every year, it experiences a significant increase. An increase in digital-based transactions (e-commerce) can help increase business sales. The business currently being carried out, especially among young people, is the thrifting business (used goods). The Pandeglang thrift store, which was established in April 2021, is a store that sells both imported and non-imported used clothing. Pandeglang thrift store sales are currently offline and online. The problem faced by Pandeglang Thrift Stores is the need for an appropriate information system for Pandeglang Thrift stores, which experiences an increase in the sales process every day. Therefore, Pandeglang thrift stores need an information system that can assist in promoting products and managing the transaction process. Toko Thrift Pandeglang's website interface is designed based on user needs by adapting the WSDM (Website Design Method) approach. The prototype created is then tested using usability testing, namely the system usability scale (SUS). The test results stated that the Thrift Pandeglang Store website prototype had met the user's needs. In addition, the evaluation results noted that the Thrift Pandeglang Shop website prototype had excellent usability with a system usability scale score of 91.01.